Significance of financial literacy on Halal business among women entrepreneur - Fatah Yasin, Raudlotul Firdaus; Mahmud, Mek Wok; Diniyya, Aulia Arifatu (2019)
Muslim women have created a unique space for them in the economy by advocating halal entrepreneurship. In Muslim minority countries, Muslim women are struggling to gain acknowledgement from society and face multiple challenges, including limitations in performing halal business activities. Besides the gender gap that is prevalent globally, Muslim women often engage in business due to the lack of job opportunities. Women with limited knowledge about business are running their businesses based on their informal managerial experience and little understanding of financial literacy.